CHARACTERISTICS OF INTERNET USE AMONGST ITALIAN UNIVERSITY STUDENTS - Marazziti, Donatella; Baroni, Stefano; Mucci, Federico; Piccinni, Armando; Ghilardi, Alberto; Fiorillo, Andrea; Massimetti, Gabriele; Luciano, Mario; Sampogna, Gaia; Moroni, Ilenia; Dell’Osso, Liliana (Psychiatria Danubina, 2020)
Problematic Internet use (PIU), that may be defined as the inability to control one's use of Internet with negative consequences in daily life, is an emerging problem involving primarily, but not only young generations. Different studies have shown that students are particularly vulnerable to PIU. Given the paucity of information on PIU in our country, the aim of this paper was at investigating the characteristics of PIU amongst Italian University students. A self-assessment questionnaire, referred by the acronym QUNT ("Questionario sull'Utilizzo delle Nuove Tecnologie"), composed by 101 items grouped together to identify a series of factors, was developed and sent through e-mail invitation to several students from three Italian Universities. The returned questionnaires were 3324, out of a total of 51,304 sent, with no difference between the two sexes. On the contrary, the distribution of the QUNT factors was different in the two sexes, in people living alone and in overweight subjects. Men resulted to be more involved in online recreational activities, whereas women seemed more attracted to instant messaging and generally to social networks. PIU was significantly more present in men than women. The comparisons of QUNT factor scores in the four BMI categories showed that the greater the BMI the greater the score of some factors. The findings of the present study indicate that the use of Internet through new technologies may exceed its real utility amongst Italian university student, with some sex-related differences. Men seem more prone to use Internet for passing time and women for social relationships. Men are also at risk of developing PIU. Again, Internet use might be a basic vulnerability factor of increasing weight gain and obesity amongst young people.